2019
DOI: 10.36565/jab.v8i1.107
|View full text |Cite
|
Sign up to set email alerts
|

Karakteristik Ibu Yang Mengalami Depresi Dalam Kehamilan

Abstract: Depression in pregnancy is a mood disorder with symptoms of feeling sad, more sensitive so easily irritated even to crying, anxiety, lack of hope for the future, sleep disturbances in the form of nightmares or insomnia, decreased appetite, decreased libido, impaired social interaction, tired easily so that they experience interference in carrying out daily activities, impaired memory or difficulty concentrating, even some mothers experience hallucinations that risk the injury to themselves and others around th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…Kehamilan dapat melibatkan penyakit pada sistem limbik, basal ganglia, hipotalamus, dan variabel hormonal berupa gangguan mood. kondisi ibu antara lain tekanan darah tinggi, hepatitis, HIV, DMG, dan lainlain (Kusuma 2019).…”
Section: Pendahuluanunclassified
“…Kehamilan dapat melibatkan penyakit pada sistem limbik, basal ganglia, hipotalamus, dan variabel hormonal berupa gangguan mood. kondisi ibu antara lain tekanan darah tinggi, hepatitis, HIV, DMG, dan lainlain (Kusuma 2019).…”
Section: Pendahuluanunclassified
“…Pada tahun 1998-2001, di Indonesia seperti di DKI Jakarta, DI Yogyakarta dan Surabaya ditemukan angka kejadiannya 11-30% (Nasri, 2017). Kusuma (2019), menyatakan 25% ibu yang baru pertama melahirkan mengalami depresi pasca melahirkan yang berat dan pada ibu yang melahirkan anak selanjutnya sekitar 20%. Penelitian Indriasari (2017) dari 55 responden ibu postpartum terdapat 53% mengalami depresi ringan, 33% tidak mengalami depresi, 9% mengalami depresi berat dan 5% mengalami depresi sedang.…”
Section: Pendahuluanunclassified
“…2 Research conducted in Jakarta revealed that pregnant women in the third trimester experienced mild depression at 26.4% and moderate depression at 6.9%. 3 Depression in pregnancy can harm the health of the mother, fetus, and family during pregnancy and after birth. Among the effects of depression are disrupting the growth and development of the fetus, the risk of bleeding during pregnancy, the risk of abortion, premature birth, and low birth weight babies.…”
Section: Introductionmentioning
confidence: 99%
“…Among the effects of depression are disrupting the growth and development of the fetus, the risk of bleeding during pregnancy, the risk of abortion, premature birth, and low birth weight babies. 3 Pregnancy, giving birth, and becoming a mother are a physiological condition of a woman. These events can give a different meaning to each woman.…”
Section: Introductionmentioning
confidence: 99%